1984
DOI: 10.1002/mrc.1270221102
|View full text |Cite
|
Sign up to set email alerts
|

13C NMR studies of methylnucleosides

Abstract: The "C chemical shifts of 22 methylated ribonucleosides and deoxyribonucleosides have been measured and assigned. The chemical s h i f t ditierences between methylated and unmodified nucleosides are correlated with their characteristic modifications of structure. The significance of the chemical shift and tautomeric variations is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
17
1

Year Published

1985
1985
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 21 publications
5
17
1
Order By: Relevance
“…However, unlike singly substituted N 6 -dA derivatives, which exhibit one- proton signal at ~ 8 ppm corresponding to the exocyclic amino group, spectra of compounds 2a-base , 2b-base , and 2c-base lacked the N 6 -H proton signal, consistent with bis -alkylation of the N 6 position of adenine. 13 C chemical shifts of the aromatic part of the molecule were similar to those reported for other N 6 -alkyladenines (45,51). NMR spectra of compounds 2a-base and 2b-base were identical, consistent with their enantiomeric relationship.…”
Section: Resultssupporting
confidence: 82%
“…However, unlike singly substituted N 6 -dA derivatives, which exhibit one- proton signal at ~ 8 ppm corresponding to the exocyclic amino group, spectra of compounds 2a-base , 2b-base , and 2c-base lacked the N 6 -H proton signal, consistent with bis -alkylation of the N 6 position of adenine. 13 C chemical shifts of the aromatic part of the molecule were similar to those reported for other N 6 -alkyladenines (45,51). NMR spectra of compounds 2a-base and 2b-base were identical, consistent with their enantiomeric relationship.…”
Section: Resultssupporting
confidence: 82%
“…In order to relate further the ultraviolet spectral and p determinations to specific changes in the structure of 8-OH-dG, the positions affected at each pK& were determined by recording 13C NMR spectra at various pH's (Figure 4). The largest effects are due to N1-C6 and N7-C8 ionizations, in accordance with the tautomeric changes that accompany these modifications (26,27). Thus, the C6 resonance exhibited a significant downfield chemical shift of 6.28 ppm from pH 7.4 to 9.3 consistent with the pK&1 (8.6), which confirms the locale of the first ionization.…”
Section: Methodssupporting
confidence: 69%
“…Accumulation of I3C nmr data has shown that C2' of a nucleoside always exhibits a lower chemical shift than C3', contrary to the recent announcement by Chang et al (6) who assigned "C chemical shifts of methylated nucleosides based on wrong assignments of C2' and C3' of adenosine.…”
mentioning
confidence: 82%